The Role of fraud management policies in mitigating the severity and reporting of fraud cases in the public sector: the case of county governments in Western Kenya - Onyango, Brian Omondi (Strathmore University, 2022)
In the twenty-first century, fraud has become a problem that management and other stakeholders are working hard to resolve. In the Kenyan County Governments, fraud is on the rise, despite ongoing efforts by the office of the auditor general and other state investigative agencies to combat it. This study sough to investigate the role of fraud management policies in mitigating the severity and reporting of fraud cases in the public sector in 11 selected county governments in western Kenya. More specifically, the study sought to investigate the role fraud control plans, mechanisms for reporting fraud and zero-tolerance to fraud policies influence the severity and reporting of fraud cases. The study borrowed from the fraud triangle and deterrence theory to address the general objective. Guided by a positivist research paradigm, primary data using a drop and pick questionnaire were collected from 316 respondents from the 11 county governments who included accountants, external and internal auditors and forensic investigative personnel. The data were analyzed using principal component-factor analyses, spearman correlations and ordered logistic regression approaches. The relevant descriptive and inferential statistics were also employed in the analyses. According to the results, two important fraud management aspects were established: deterrence effect of fraud management policies and fraud case reporting instances. The results illustrate that having an anti-fraud plan with zero tolerance to fraud, an independent fraud reporting system and deploying an integrated macro policy in the fight against fraud are useful mechanisms in deterring and combating the risk of fraud. The results also show that installing a fraud reporting system with real consequences to the offenders leads to an increase in the reporting of fraud cases. In line with the results, a strict anti-fraud plan with zero tolerance to fraud is useful in encouraging more fraud cases to be reported. Further, the deployment of an integrated macro policy on fraud might lead to reduced fraud case reporting. According to the study's findings, county governments in Kenya should adopt fraud management policies to assist in reducing the severity of fraud and help in timely reporting and handing of fraud cases. The findings are useful in informing fraud risk management policies in the counties as well as other public sector entities.
A Thesis submitted in partial fulfilment of the requirements for the award of Degree of Master of Commerce at Strathmore University